Strategi Pengembangan Industri Kreatif Kain Tenun Lejo Sebauk Pada Masa Pandemi COVID-19 - Azrani Azrani; Hutomo Atman Maulana (Universitas Islam Kadiri, 2021)
This study aimed to determine the development strategy of Lejo's weaving creative industry at Small and medium-sized enterprises (SMEs) Tenun Putri Mas during the pandemic Covid-19. This research used descriptive qualitative method which is explained systematically and clearly illustrated. Data collection techniques were carried out by interviews, observations, and documentation which were carried out from March to June 2020, during the Covid-19 pandemic in Indonesia. The data analysis technique used in this research is qualitative analysis which consists of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the creative industry development strategy can be applied to the weaving of Putri Mas is a market development strategy, product development strategy, and innovation strategy. Efforts to apply the development strategy of the creative industry of Lejo Woven Fabric in SME’s Putri Weaving in the form of the use Instagram, Facebook, Line, and Whatsapp. Diversifying products such as dispenser covers, table tops, curtains and TV covers. Innovating motifs on products such as the ant motif with beriring, poor cloud motifs, and the duck motif back home in the evening. Constraints in applying the development strategy are the limitations of human resources, raw materials, and product development costs. The solution to face obstacles is to increase human resources, add raw material suppliers, and propose micro business financing.